2021
DOI: 10.1111/jir.12833
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating working memory outcome measures for children with Down syndrome

Abstract: Background There is a critical need for the psychometric evaluation of outcome measures to be used in clinical trials targeting cognition in Down syndrome (DS). This study examines a specific cognitive skill that is of particular importance in DS, working memory, and the psychometric properties of a set of standardised measurements to assess working memory in individuals with DS. Methods Ninety children and adolescents ages 6 to 18 years old with DS were assessed on a selection of verbal and visuospatial worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…In this special issue, Schworer et al . (2022) present a comprehensive account of the psychometric properties of some of the most commonly‐used measures to assess working memory in people with Down syndrome. They found that several of these measures met their a priori criteria for reliability, validity and feasibility for their entire sample of children and adolescents with Down syndrome.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…In this special issue, Schworer et al . (2022) present a comprehensive account of the psychometric properties of some of the most commonly‐used measures to assess working memory in people with Down syndrome. They found that several of these measures met their a priori criteria for reliability, validity and feasibility for their entire sample of children and adolescents with Down syndrome.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Two parents reported that their child had ASD. Data from the participants in this study have been used in other manuscripts focused on the assessment of working memory outcome measures [33] and the association between executive function and adaptive skills [34].…”
Section: Participantsmentioning
confidence: 99%
“…Feasibility criteria were set a priori and ≥80% was the selected parameter for acceptable feasibility for use of these measures in DS research. This selection was informed by previous work on the psychometrics of cognitive measurements in intellectual disability and DS [33,39]. Examiners recorded reasons for noncompletion, which consisted of not understanding the task, behavioral noncompliance, and verbal refusal.…”
Section: Analysis Planmentioning
confidence: 99%
See 2 more Smart Citations